Planning organization and methods in the Philippines lessons from experience - Encarnacion, Teodoro T. (1976)
This article traces the institutional evolution of planning techniques with references to an experiment which was designed to overcome deeply felt deficiencies in past planning approaches. The experiment was in the form of an interdisciplinary ad hoc planning group organized in collaboration with the bureaucracy and the academic community. It sought to establish a "more rational and workable planning and decision-making mechanism" in response to planning inadequacies. The group came up with a "pragmatic approach" which assured that programs are closely attuned to basic community needs and that the effectiveness of these programs is measured by how well they improve the lot of the community, rather than by how technologically efficient the projects are planned, implemented and operated. This experimental group, however, will eventually be phased out.
Keywords: Public administration -- Decision making; Public administration -- Management; Program transformation